E Effect of Cognitive, Afective, Conative and E-Satisfaction on Repurchase Intention - Mutia Tri Satya; Arindra Khrisna Karamoy; Listiawati; Abdul Fidayan (Institute of Computer Science (IOCS), 2021)
Online Shop or shopping for goods or services has become a common thing to see. Indonesia has changed the flow of trade in the business world to become completely digital. Therefore, it is important for online business people to understand things that can create customer satisfaction and loyalty. This study aims to find out how cognitive, affective, conative, and e-satisfaction influence on repurchase intention. The method used in this research is to use factor analysis with 150 respondents.